Annual cycles of phytoplankton biomass in the subarctic Atlantic and Pacific Ocean. Issue 2 (5th February 2016) - Westberry, Toby K.; Schultz, Patrick; Behrenfeld, Michael J.; Dunne, John P.; Hiscock, Michael R.; Maritorena, Stephane; Sarmiento, Jorge L.; Siegel, David A.
Abstract: High‐latitude phytoplankton blooms support productive fisheries and play an important role in oceanic uptake of atmospheric carbon dioxide. In the subarctic North Atlantic Ocean, blooms are a recurrent feature each year, while in the eastern subarctic Pacific only small changes in chlorophyll (Chl) are seen over the annual cycle. Here we show that when evaluated using phytoplankton carbon biomass (Cphyto ) rather than Chl, an annual bloom in the North Pacific is evident and can even rival blooms observed in the North Atlantic. The annual increase in subarctic Pacific phytoplankton biomass is not readily observed in the Chl record because it is paralleled by light‐ and nutrient‐driven decreases in cellular pigment levels (Cphyto :Chl). Specifically, photoacclimation and iron stress effects on Cphyto :Chl oppose the biomass increase, leading to only modest changes in bulk Chl. The magnitude of the photoacclimation effect is quantified using descriptors of the near‐surface light environment and a photophysiological model. Iron stress effects are diagnosed from satellite chlorophyll fluorescence data. Lastly, we show that biomass accumulation in the Pacific is slower than that in the Atlantic but is closely tied to similar levels of seasonal nutrient uptake in both basins. Annual cycles of satellite‐derived Chl and Cphyto are reproduced by in situ autonomous profiling floats. These results contradict the long‐standing paradigm that environmental conditions prevent phytoplankton accumulation in the subarctic Northeast Pacific and suggest a greater seasonal decoupling between phytoplankton growth and losses than traditionally implied. Further, our results highlight the role of physiological processes in shaping bulk properties, such as Chl, and their interpretation in studies of ocean ecosystem dynamics and climate change. Key Points: Satellite‐retrieved phytoplankton carbon shows similar annual cycles across subarctic ocean basins Phytoplankton physiological changes mitigate the annual biomass signal in the chlorophyll record Biomass accumulation rates in both basins are closely tied to nutrient drawdown